Blood Cholesterol and Glucose of KUB Chicken That Feed Containing Chinese Cabhage (Brassica pekinensia L.) - Lusfia Lusfia; muhammad amrullah Pagala; Hamdan Has (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
This study aimed to analyze the levels of Blood cholesterol, and glucose of KUB chicken that feed containing Chinese cabbage (Brassica pekinensia L.) The design used in this study was a completely randomized design (CRD) consisting of 4 treatments and 5 replications.  The treatments used were: P1 = control, P2 = ration + 3% chicory flour, P3 = ration + 6% chicory flour, P4 = ration + 9% chicory flour.  The parameters observed in this study were cholesterol and glucose levels.  Based on the results of the study, the addition of chicory flour had no significant effect (P>0.05) on blood glucose in KUB chickens and a significant effect (P˂0.05) on blood cholesterol levels in KUB chickens.